2021
DOI: 10.3390/catal11121428
|View full text |Cite
|
Sign up to set email alerts
|

Research on Coal Tar Pitch Catalytic Oxidation and Its Effect on the Emission of PAHs during Co-Carbonation with Coal

Abstract: Coal tar pitch (CTP) is abundant and widely used, but its properties will be affected due to oxidation aging during storage. In this study, CTP was oxidized by simulating the air oxidation process, and the change of chemical structure has been analyzed by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and both gas chromatography and mass spectrometry (GCMS). The effects of the oxidized and unoxidized CTP co-carbonization with coal on the polycyclic aromatic hydrocarbons (PAHs) emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…In addition, increased intensity of FT-IR signals were also observed at 2860 and 2930 cm −1 , which can be indexed to the cyclohexane bands [ 82 ]. These results are in good agreement with the benzaldehyde ( m / z = 106) and dimethylcyclohexane ( m / z = 112) products recorded by GC-MS ( Table 3 ) [ 83 ]. It should be noted that the conversion rates based on GC-MS are slightly higher than that of UV-vis DRS, since some side products might not be reflected by absorption spectra.…”
Section: Resultssupporting
confidence: 88%
“…In addition, increased intensity of FT-IR signals were also observed at 2860 and 2930 cm −1 , which can be indexed to the cyclohexane bands [ 82 ]. These results are in good agreement with the benzaldehyde ( m / z = 106) and dimethylcyclohexane ( m / z = 112) products recorded by GC-MS ( Table 3 ) [ 83 ]. It should be noted that the conversion rates based on GC-MS are slightly higher than that of UV-vis DRS, since some side products might not be reflected by absorption spectra.…”
Section: Resultssupporting
confidence: 88%
“…The spectrum of all samples had strong bands between 3000 and 2800 cm –1 , as shown in Figure a–f. At 2920 and 2850 cm –1 , the stretching vibration peak of aliphatic C–H and the antisymmetric stretching vibration peak of saturated C–H on methyl (−CH 3 ) were respectively, and the stability of the peak indicated that the aliphatic content had not increased …”
Section: Results and Discussionmentioning
confidence: 99%
“…At 2920 and 2850 cm −1 , the stretching vibration peak of aliphatic C−H and the antisymmetric stretching vibration peak of saturated C−H on methyl (−CH 3 ) were respectively, 15 and the stability of the peak indicated that the aliphatic content had not increased. 16 3. 17 The range of 1620−1500 cm −1 represents the C�C tensile vibration peak.…”
Section: Ftir Analysis Of Heavy Coal Tar Cut By Different Fractions 3...mentioning
confidence: 99%
“…During baking, the pitch carbonizes, which binds the coke particles together. However, the quality and availability of anode-grade raw materials have decreased. …”
Section: Introductionmentioning
confidence: 99%